Safety and Outcomes of Permanent and Retrievable Inferior Vena Cava Filters in the Oncology Population. (5th February 2020) - Shaikh, Saba S.; Kamath, Suneel D.; Ghosh, Debashis; Lewandowski, Robert J.; McMahon, Brandon J.
Abstract : Background . The role for inferior vena cava (IVC) filters in the oncology population is poorly defined. Objectives . Our primary endpoint was to determine the rate of filter placement in cancer patients without an absolute contraindication to anticoagulation and the rate of recurrent VTE after filter placement in both retrievable and permanent filter groups. Patients / Methods . A single-institution, retrospective study of patients with active malignancies and acute VTE who received a retrievable or permanent IVC filter between 2009-2013. Demographics and outcomes were confirmed on independent chart review. Cost data were obtained using Current Procedural Terminology (CPT) codes. Results . 179 patients with retrievable filters and 207 patients with permanent filters were included. Contraindication to anticoagulation was the most cited reason for filter placement; however, only 76% of patients with retrievable filters and 69% of patients with permanent filters had an absolute contraindication to anticoagulation. 20% of patients with retrievable filters and 24% of patients with permanent filters had recurrent VTE. The median time from filter placement to death was 8.9 and 3.2 months in the retrievable and permanent filter groups, respectively. The total cost of retrievable filters and permanent filters was $2, 883, 389 and $3, 722, 688, respectively. Conclusions . The role for IVC filters in cancer patients remains unclear as recurrent VTE is common and time from filter placement to death is short. Filter placement is costly and has a clinically significant complication rate, especially for retrievable filters. More data from prospective, randomized trials are needed to determine the utility of IVC filters in cancer patients.